Survey on the Analysis of Students' Arithmetic Ability at the Senior High School Level (SMA) - Hafiz, Muhammad; Anisa, Yuan (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study aims to assess the arithmetic skills of high school students in Grade X at a senior high school in Langkat Regency. The sample consists of 30 Grade X students, selected using a purposive sampling technique. All samples were given a written test to measure their arithmetic skills. Based on the results, it was concluded that the overall arithmetic ability scored 46.5, categorized as sufficient. However, when viewed from a percentage perspective, it remains concerning as many students still demonstrate poor arithmetic skills. The solutions proposed by the researcher to address the challenges faced by Grade X high school students in arithmetic skills are as follows: implementing learning approaches based on the principles of mathematics education, such as cooperative learning models; reinforcing concepts that students have not yet understood; and providing practice questions related to arithmetic. After the teaching and learning process, a proposed solution to address students' learning difficulties is to offer remedial mathematics instruction based on the principles of mathematics education, focusing on building a strong foundation in arithmetic concepts.